PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI MIPA SMAN 2 LUBUK BASUNG - ULFI WADDANI YUNI (Departemen Matematika, 2020)
Abstract—.Problem solving capability is the goal of learning mathematics, but in reality the ability to solve the mathematical problem of participants is still low. The application of inquiry learning model is is one of the efforts that can be done to overcome the problem. The type of research used is quasy-experimental research with the research design of The Static Group Design. Based on the results of data analysis of the final test the research ,it was concluded that there is an influence on the application of inquiry learning model to the ability of mathematical students problem solving, so that mathematical problem solving skills of students who learn with inquiry learning model are better than those of mathematical problem solving skills of students who learn with the direct learning Model. Keywords — Inquiry learning model, Mathematics learning, Mathematical problem solving skills.